Alpha-diversity is strongly influenced by the composition of other samples when using multiplexed sequencing approaches. (December 2018) - Bissett, Andrew; Brown, Mark V.
Abstract: Microbial alpha-diversity, a fundamental ecological concept, is often determined using multiplexed amplicon sequencing approaches. Here we show, using standardized controls and 1879 soil samples, across 21 illumina MiSEQ high throughput sequencing (HTS) runs, that sample alpha-diversity estimates are highly dependent upon the overall diversity of all samples within the sequencing run, a likely result of within sequencing run cross-talk. Cross-talk, therefore, has grave implications for alpha-diversity interpretation in mulitplexed sequencing studies. Highlights: Microbial alpha-diversity, a fundamental ecological concept, is often determined using multiplexed amplicon sequencing approaches. Alpha-diversity is highly dependent upon the overall diversity of all samples within the sequencing run.